Pembuatan Surat Izin Usaha Perdagangan Bagi Perseroan Terbatas Dengan Terbitnya Peraturan Pemerintah Nomor 29 Tahun 2016 - Wibawa, Anak Agung Bagus Putra (Acta Comitas : Jurnal Hukum Kenotariatan, 2019)
The issuance of Government Regulation Number 29 Year 2016 concerning Changes in the Authorized Capital of Limited Liability has an impact on the founders of the company related to the cost reduction of the establishment of a Limited Liability Company which gives freedom to the founders of the company in determining the legal basis of a Limited Liability Company. Limited Liability Company is a company that carries out trading activities. Every company that carries out trading activities is obliged to take care of the Trade Business License. The making of Trade Business License is regulated in the Minister of Trade's Regulation No. 46 / M-DAG / PER / 9/2009 concerning Issuance of Trading Business License. One of the conditions is to have a wealth of Rp 50,000,000 (fifty million rupiah). From this regulation arises a norm conflict between the Government Regulation and the Ministerial Regulation. The problems arising from this research are the process of establishing a limited company and how is the legal implication of establishing a limited company in making a trade business license with government regulation number 29 of 2016. This research is a normative study with a legal approach and a legal concept analysis approach. The process of establishing a limited liability company is by ordering the name of the company online, then making the deed of establishment of a Limited Liability Company with the conditions set. After all is fulfilled, then the registration is done online on the web https://www.ahu.go.id. the legal implications of establishing a Limited Company in making Trade Business License with Government Regulation Number 29 of 2016 is that the company's founder can make Trade Business License with an authorized capital based on the agreement of the company's founders. Terbitnya Peraturan Pemerintah Nomor 29 Tahun 2016 tentang Perubahan Modal Dasar Perseroan Terbatas berdampak pada pendiri perseroan terkait keringanan biaya pendirian Perseroan Terbatas (PT) yang memberikan kebebasan bagi para pendiri perseroan dalam menentukan bersaran modal dasar Perseroan Terbatas. Perseroan Terbatas merupakan perusahaan yang didalamnya melakukan kegiatan perdagangan. Setiap perushaaan yang melakukan kegiatan perdagangan wajib untuk mengurus Surat Izin Usaha Perdangan (SIUP). Pembuatan SIUP diatur dalam Perautran Menteri Perdagangan Republik Indonesia Nomor 46/M-DAG/PER/9/2009 tentang Penerbitan Surat Izin Usaha Perdagangan. Salah satu syaratnya adalah memiliki kekayaan sebesar Rp 50.000.000, (lima puluh juta rupiah). Dari peraturan tersebut timbul konflik norma antara Peraturan Pemerintah dengan Peraturan Menteri tersebut. Adapun permasalahan yang timbul dari penelitian ini adalah Bagaimanakah Proses Pendirian Persoran Terbatas dan Bagaimanakah Implikasi Hukum Pendirian Perseoran Terbatas Dalam Membuat Surat Izin Usaha Perdagangan dengan Peraturan Pemerintah Nomor 29 Tahun 2016. Penelitian ini berupa penelitian normatif dengan pendeketan undang-undang dan pendekatan analisis konsep hukum. Peroses pendirian perseroan terbatas yaitu dengan memesan nama perseroan secara online, lalu pembuatan akta pendirian Perseroan Terbatas dengan syarat-syarat yang telah diatur. Setelah semua terpenuhi baru dilakukan pendaftarkan melalui online di web https://www.ahu.go.id. implikasi hukum pendirian Perseoran Terbatas dalam membuat SIUP dengan Peraturan Pemerintah Nomor 29 Tahun 2016 adalah pendiri perseroan dapat membuat SIUP dengan modal dasar kesepakatan para pendiri perseroan.